Development of a Squelch Effect in Adult Patients After Simultaneous Bilateral Cochlear Implantation. Issue 9 (October 2016) - Kraaijenga, Véronique J. C.; van Zon, Alice; Smulders, Yvette E.; Ramakers, Geerte G. J.; Van Zanten, Gijsbert A.; Stokroos, Robert J.; Huinck, Wendy J.; Frijns, Johan H. M.; Free, Rolien H.; Grolman, Wilko
Abstract : Objectives: To investigate whether a squelch effect occurs in the first 3 years after simultaneous bilateral cochlear implantation and to investigate whether this effect increases during follow-up. Study Design: Prospective study as part of a multicenter randomized controlled trial that compares simultaneous bilateral cochlear implantation to sequential and unilateral cochlear implantation. Setting: Tertiary referral center. Patients: Nineteen postlingually deafened adults. Intervention: Simultaneous bilateral cochlear implantation. Main Outcome Measure: The squelch effect, measured yearly with a speech-intelligibility-in-noise test with spatially separated sources. Bilateral results were compared to unilateral results in which the cochlear implant at the noise side was turned off. The squelch effect was investigated for the patients' best performing ear and for the left and right ears separately. Results: In 13 individual patients, a squelch effect was present after 1 year. This number increased during follow-up years. On group level, a squelch effect was present in patients' best performing ear after 2 and 3 years (1.9 dB). A squelch effect was present in both ears after 3 years (AS: 1.7 dB, AD: 1.3 dB). Conclusion: Patients who underwent simultaneous bilateral cochlear implantation developed a measurable benefit from the squelch effect after 2 years in their best performing ear and after 3 years in both ears. These observations suggest that the brain learns to use interaural differences to segregate sound from noise after simultaneous bilateral cochlear implantation. The squelch effect increased over time which suggests a growth in cortical integration and differentiation of inputs from bilateral CIs due to brain plasticity. Trial Registration: Dutch Trial Register NTR1722. Level of evidence: 1b.